Are tablets a practical source of protein substitute in phenylketonuria?. Issue 4 (1st April 2003) - MacDonald, A; Ferguson, C; Rylance, G; Morris, A A M; Asplin, D; Hall, S K; Booth, I W
Abstract : Background: A phenylalanine-free amino acid based protein substitute is necessary to provide the major source of protein in phenylketonuria (PKU). Protein substitutes in PKU are usually given as drinks. These are unpalatable and compliance is often poor. Tablets containing a suitable mixture of phenylalanine-free amino acids (Aminogran Food Supplement, UCB) are now available. Aims: To compare the effectiveness and acceptability of these tablets with conventional protein substitute drinks. Methods: Twenty one subjects with PKU, aged 8–25 years, participated in a randomised crossover study. During one phase, subjects received at least 40% of their protein substitute requirements from the amino acid tablets and the rest from their usual protein substitute tablets. During the other phase, they received their usual protein substitute. Each period lasted 12 weeks. Blood phenylalanine concentrations were measured at least once every two weeks and other plasma amino acids were measured at the beginning, at crossover, and at the end of the study. The subjects kept a diary of all protein substitute taken. Results: Compliance appeared to be better with the new tablets than with patients' usual protein substitutes. Ninety per cent (18/20) recorded that they took the tablets as prescribed, compared with 65% (13/20) fully compliant with their usual protein substitute. Moreover, plasma phenyalanine was lower on the amino acid tablets, and the median difference in blood concentrations between the two groups was 46 μmol/l (95% CI 14.8 to 89.0, p = 0.02). Tyrosine increased by a median of 16 μmol/l daily on the amino acid tablets (95% CI 7.1 to 40.5, p = 0.01). Most subjects (70%) preferred incorporating the new tablets into their usual protein substitute regimen. Conclusions: Amino acid tablets are an effective and relatively popular protein substitute in older children, teenagers, and adults with PKU.